Pleural thickening induced by Glaesserella parasuis infection was linked to increased collagen and elastin - Gong, Huimin; Chen, Liying; He, Yanling; Hua, Kexin; Ma, Bin; Gao, Yuan; Xu, Xiaojuan; Hu, Xueying; Jin, Hui (Frontiers in Cellular and Infection Microbiology, 2022)
Glaesserella parasuis is well-known for causing Glässer’s disease, which costs the worldwide swine industry millions of dollars each year. It has been reported the symptom of pleural thickening during Glässer’s disease but this symptom has received little attention. And there is no research on the elements which promote pleural thickening. In this study, pleural thickening was discovered to be associated with increased collagen fibers and elastic fibers. Furthermore, collagen-I and elastin were found to be up-regulated and concentrated in the pleura at the mRNA and protein levels following infection. To summarize, our findings add to the theoretical understanding of Glässer’s disease and provide strong support for further research into the pathogenic mechanism of Glaesserella parasuis and the program’s target treatment.